South Africa's Future - Ginsberg, A. author. aut Link
X, 260 p.
Keywords: Unemployment is growing. Crime is on the increase. The currency has fallen. The initial euphoria following South Africa's transition to democracy is waning as people become disillusioned with the state of the economy and government's lack of delivery on polices and promises. Where does South Africa go from here? It is not all doom and gloom and there is hope for the future. Anthony Ginsberg offers solutions to the fundamental problem of rising unemployment, crime, homelessness and poverty, all excerbated by high taxes, draconian tariffs and stagnant foreign investment. He encourages us to become informed and aware before we criticise. This book is aimed at everyone interested in contributing to South Africa' s future as a prosperous nation in the benefit of all her citizens.